(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cardiovascular complications are the leading cause of morbidity and mortality in children with chronic kidney disease (CKD). Structural and functional cardiac changes may begin early in the disease course, even before dialysis initiation. Early identification of cardiovascular involvement is essential for improving outcomes in pediatric CKD patients. Methodology: This observational study was conducted in the Department of Paediatrics, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from March 2025 to November 2025. Children aged 1–18 years with CKD were included and categorized into those on dialysis and those not on dialysis. Clinical evaluation, routine investigations, ambulatory blood pressure monitoring, and echocardiography were performed. Parameters assessed included left ventricular mass (LVM), ejection fraction, fractional shortening, and ambulatory blood pressure. Statistical analysis was done using Student’s t-test and Chi-square test, with p<0.05 considered significant. Results: A total of 60 children were studied (46 non-dialysis and 14 dialysis). Left ventricular mass was significantly higher in dialysis patients (131.71 ± 59.06 vs 98.91 ± 49.61, p=0.042). Ejection fraction and fractional shortening were significantly lower in the dialysis group (p=0.006 and p=0.007 respectively). Ambulatory blood pressure was higher in dialysis patients but not statistically significant. No strong correlation was found between CKD duration and LVM. Conclusion: Children with CKD, especially those on dialysis, have significant cardiovascular abnormalities. Early screening and regular cardiac evaluation are essential to reduce long-term complications.